Resetting and annihilating reentrant waves in a ring of cardiac tissue: Theory and experiment - Gonzalez, H; Nagai, Y; Bub, G; Glass, L; Shrier, A (2000)
Theory predicts that a stimulus delivered to an excitation wave circulating on a ring of excitable media will either have no effect, or it will reset or annihilate the excitation depending on the phase and magnitude of the stimulus. We summarize the basis for these theoretical predictions and demonstrate these phenomena in an experimental system consisting of a tissue culture of embryonic chick heart cells cultured in the shape of a ring.